Effect of Psychoeducation on Caregivers’ Burden of Patients Suffering from Obsessive Compulsive Disorder (Journal of Fatima Jinnah Medical University, 2024)
Background: In chronic mental disorders a considerable burden is placed on persons involved in care. Therapeutically, an evidence-based intervention for patients and their families is psychoeducation that provides information and support to help such individuals having a better understanding of the illness to cope well with it. The objective of study was to determine the effect of psychoeducation on caregivers’ burden of patients suffering from obsessive-compulsive disorder.Subjects and methods: A randomized double-blinded controlled trial was conducted at the psychiatry department of Sir Ganga Ram Hospital on 80 caregivers having scores above 23 on the family burden interview schedule and did not have any psychoeducation session in the previous 6 months. They were divided into two equal groups (40 each). The intervention group received four psychoeducation sessions for one month and the control group was not provided psychoeducation sessions. At the end of four weeks, the family burden interview schedule scores were noted down on proforma and SPSS version 23.0 was used to enter and analyze the data.Results: The mean age of participants in the intervention versus control group was 28 + 4.84 vs. 29 4.62 years. With respect to gender, in the interventional group, there were 18 (24%) males and 20 (26.7%) females and in the control group there were 14 (18.7%) males and 23 (30.7%) females There was a significant difference in mean FBIS score at 4 weeks was 21 4.29 and 33 5.87 respectively (p-value
Keywords: Obsessive compulsive disorder; Caregiver; Burden